IL2rg Cytokines Enhance Umbilical Cord Blood CD34+ Cells Differentiation to T Cells - Zeynab Aliyari; Sara Soleimanirad; Manizheh Sayyah Melli; Hamid Tayefi Nasrabadi; Hojjatollah Nozad Charoudeh (Tabriz University of Medical Sciences, 2015)
Purpose: Umbilical cord blood (UCB) is an alternative source of hematopoietic stem cell (HSC) transplantation for the treatment of patients with leukemia if matched donor is not available. CD34+ is a pan marker for human hematopoietic stem cells, including umbilical cord blood stem cell. In comparison to other sources, cord blood CD34+ cells proliferate more rapidly and produce large number of progeny cells. For ex vivo expansion of Umbilical Cord Blood- HSCs/HPCs, different combinations of cytokines have been used in many laboratories. IL2rg cytokines, including IL2, IL7 and IL15, are key cytokines in the regulation of differentiation, proliferation and survival of immune cells. IL2 is important cytokine for T cell survival and proliferation, IL7 involve in B cell development and IL15 is a key cytokine for NK cell development. In this study we evaluated the generation of T cells derived from CD34+ and CD34- cord blood mononuclear cells by using combination of cytokines including IL2, IL7 and IL15. Methods: Cultured cord blood mononuclear cells were evaluated at distinct time points during 21 days by using flow cytometry. Results: Present study showed that differentiation of T cells derived from CD34+ cord blood mononuclear cells increased by using IL2 and IL7 at different time points. In the other hand IL15 did not show any significant role in generation of T cells from CD34+ cord blood mononuclear cells. Conclusion: Taken together, our data illustrated that either IL2 or IL7 versus other cytokine combinations, generate more T cell from cord blood CD34 cells, probably this cytokines can be the best condition for ex vivo expansion of UCB HSCs.